Action Research, knowledge production, and Social Work - Bordenave, Geisa; Gonçalves, Rafael Soares (Argumentum, 2024)
This article reflects on Action Research methodology and knowledge production in the field of Social Work. The theoretical and methodological reflections developed here are the result of analyses developed by the authors, both in research involving the subject and in theoretical-practical reflections developed from research linked to the Urban and Socio-environmental Studies Laboratory (LEUS) of the Social Work Department at PUC-Rio. The main aim is to reflect on Action Research methodology, the possibility of producing knowledge from it, and its connections with Social Work, considering its investigative and interventional dimension and the ethical-political project.
Keywords: Action Research; Knowledge production; Ethical-political project; The investigative dimension of Social Work